Allelopathic Influence of Sesame and Green Gram Intercrops on Cotton in a Replacement Series. Issue 1 (28th October 2016) - Shah, Adnan Noor; Iqbal, Javaid; Fahad, Shah; Tanveer, Mohsin; Yang, Guozheng; Khan, Ejaz Ahmad; Shahzad, Babar; Yousaf, Muhammad; Hassan, Waseem; Ullah, Abid; Bukhari, Muhammad Adnan; Salah, Akram; et al.
Abstract : Using a mixed culture replacement method, different plant species are planted with different densities per unit area. The benefits of using this method are evident; however, phytotoxic/competitive effects of these different plant species on each other are rarely studied, especially for cotton. Allelopathy is a biological phenomenon that can affect many aspects of plant ecology. A pot experiment was conducted to determine the individual and/or interactive effects of cotton, sesame, and green gram on each other. Sesame, green gram, and cotton were sown in a replacement series in three different combinations: Sesame–cotton (3–0, 2–1, 1–2, 0–3); sesame–green gram (3–0, 2–1, 1–2, 0–3); and cotton–green gram (3–0, 2–1, 1–2, 0–3). The experiment was conducted using a completely randomized design with four replications; results revealed that inclusion of a legume crop ( i.e ., green gram) significantly improved cotton shoot and root growth and yield, but sowing of sesame with cotton considerably decreased cotton plant performance as compared to green gram. Similarly, sesame plant height was improved by increasing the number of cotton and green gram plants per pot. The effects of sesame and cotton were deleterious for green gram. It was concluded that high‐stature crops (such as the main crop) can be grown with short‐stature leguminous crops as the companion crop. Abstract : Planting density is very crucial for intercropping. In the current study, cotton plants are intercropped with one or two plants of sesame or green gram per pot. The results shows that intercropping with green gram or sesame enhanced cotton yield as compared to sole cotton planting. Among the intercropping crops, green gram shows better results compared with sesame.